"Acute Bilateral Neuroretinitis and Panuveitis in A Patient with Coronavirus Disease 2019: A Case Report"- Few Comments. (16th March 2023) - Kawali, Ankush; Sanjay, Srinivasan; Mahendradas, Padmamalini; Shetty, Rohit
ABSTRACT: During the Coronavirus Disease 2019 (COVID-19) pandemic, we have witnessed increase in number of reports of a known uveitic entity being associated with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Causal relation is yet to be proven for many reports. Perhaps, occurrence of a previously known region-specific endemic disease or closely resembling manifestations of a known disease in a non-endemic region during the COVID-19 pandemic might suggest a causal relationship. Epidemic retinitis (ER) or post fever retinitis is such condition with geographic variation. Occurrence of ER or ER-like manifestations in a non-endemic country during the pandemic should instigate further studies to consider SARS-CoV-2 as a causative organism.